2017
DOI: 10.1021/acs.orglett.7b02829
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Counterion Effects Using a Gold Affinity Index and a Hydrogen Bonding Basicity Index

Abstract: We have developed a gold affinity index and hydrogen bonding basicity index for counterions and have used these indexes to forecast their reactivity in cationic gold catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 48 publications
1
60
1
Order By: Relevance
“…In these cases, the ability of a counterion to mediate the proton transfer (hydrogen bonding basicity) may play an important role. Indeed, in our previous investigation on the counterion effects on the gold-catalyzed reaction, we found that this was indeed the case ( Lu et al., 2017 ).
Scheme 5 A Transition State Involves an Active Proton Transfer
…”
Section: Resultsmentioning
confidence: 67%
“…In these cases, the ability of a counterion to mediate the proton transfer (hydrogen bonding basicity) may play an important role. Indeed, in our previous investigation on the counterion effects on the gold-catalyzed reaction, we found that this was indeed the case ( Lu et al., 2017 ).
Scheme 5 A Transition State Involves an Active Proton Transfer
…”
Section: Resultsmentioning
confidence: 67%
“…Screening of different mixtures of solvents as well as of different alkene to diazonium ratios showed that the reaction performed best with a mixture of 4% MeOH in toluene using 1.5 equivalents of the alkene (see Tables 1 and 2 in Supporting Information). Addition of just 5 mol% of the cationic reaction promoter KCTf 3 substantially increased the reaction yield from 63% to 77% (entries 1 and 2 from Table ) …”
Section: Resultsmentioning
confidence: 99%
“…The cationic Au I catalyst in each case was prepared in situ from equimolar quantities of the appropriate ligated AuCl and silver(I) triflimide that were delivered as standard solutions in dichloromethane . A significantly faster reaction was observed in the case of the triphenylphosphino complex (entry 1), but under identical conditions the yield of 4 was better with the aryl phosphite ligand (entry 3), so it was chosen . Since there was no significant difference between 1,2‐dichloroethane and dichloromethane (entries 3, 4) dichloromethane was selected .…”
Section: Resultsmentioning
confidence: 99%